2023
DOI: 10.3390/ijms24021807
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FGF13 as a Potential Biomarker and Target for Diagnosis of Impaired Glucose Tolerance

Abstract: Early identification of pre-diabetes provides an opportunity for intervention and treatment to delay its progression to type 2 diabetes mellitus (T2DM). We aimed to identify the biomarkers of impaired glucose tolerance (IGT) through bioinformatics analysis. The GSE76896 dataset, including non-diabetic (ND), IGT, and T2DM clinical samples, was deeply analyzed to identify 309 Co-DEGs for IGT and T2DM. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses indicated that inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…[31] In addition, some studies have argued that FGF13 has important effects on abnormal glucose tolerance through the PI3K-AKT signaling pathway. [32] A study also considered that FGF13 potentiates pathological cardiac hypertrophy via the activation of NF-κB. [33] The present study confirmed that there was a significant positive correlation between FFAR3 and G0S2 and between FGF13 and G0S2.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…[31] In addition, some studies have argued that FGF13 has important effects on abnormal glucose tolerance through the PI3K-AKT signaling pathway. [32] A study also considered that FGF13 potentiates pathological cardiac hypertrophy via the activation of NF-κB. [33] The present study confirmed that there was a significant positive correlation between FFAR3 and G0S2 and between FGF13 and G0S2.…”
Section: Discussionsupporting
confidence: 77%
“…[ 31 ] In addition, some studies have argued that FGF13 has important effects on abnormal glucose tolerance through the PI3K-AKT signaling pathway. [ 32 ] A study also considered that FGF13 potentiates pathological cardiac hypertrophy via the activation of NF-κB. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…The serum level of FGF-13 was decreased in patients with impaired glucose tolerance and T2DM compared to that in the healthy controls, suggesting that it could serve as a diagnostic marker for T2DM[ 55 ]. In addition, FGF-13 plays an important role in diabetic nephropathy[ 56 ] and obesity[ 57 ].…”
Section: Fgfs Play An Important Role In Diabetes and Related Diseasesmentioning
confidence: 99%
“…The clinical samples involved in the experiment were all from our previous studies (Chen et al, 2023b). The study was conducted according to the guidelines of the Declaration of Helsinki and approved by the Ethics Committee of Tongji Medical College, Huazhong University of Science and Technology (ChiCTR2000034751).…”
Section: Clinical Patient Selectionmentioning
confidence: 99%